Paths and challenges of new technologies: The case of nanotechnology-based cosmetics development in Brazil - Denise Barbieux; Antonio Domingos Padula (Administrative Sciences, 2018)
New technologies have challenges to overcome when applying it to new products. New products depend on the technological and market novelties. Therefore, the term product innovativeness is defined as the technological and market degree of novelty. For several industries, the nanotechnology has been the latest technology, and it has also been included in Brazilian government strategic agenda. Considering the importance of new technologies and innovation, we describe the paths and challenges of nanotechnology-based cosmetics development to achieve product innovativeness. Opposing the new product development (NPD) mainstream based on efficiency, we used the evolutionary approach by highlighting the novelties. We describe three NPD stages (conception, operationalization, nd launch). For empirical evidence, we chose two Brazilian emblematic cases (suppliers for cosmetics industry) that domain nanotechnology. One case scans more potential market novelties and consequently produces indigenous nanotechnology for international industries such as cosmetics, food, and textile. The second case represents the new technology limited by the application in cosmetics. New technologies are not an innovation guarantee. Market demands must be identified in the early stage of NPD. When the focus is the novelty, the NPD evolutionary approach is useful.
Keywords: 350; nanotechnology; cosmetics industry; product innovativeness; innovation; New Product Development; Small and Medium Enterprises